Indigenous pig genetic resources: Preliminary documentation of current status and population trend of Tswana pigs in three districts of Botswana - THUTWA, KETSHEPHAONE; CHABO, RICKS GALETSENE; KGWATALALA, PATRICK MONAMETSI; NSOSO, SHALAULANI JAMES (The Indian Journal of Animal Sciences, 2022)
This study aimed to assess the status, population and population trend of Tswana pigs in three districts of Botswana. A survey was conducted for three consecutive years from 2018 to 2020 in three districts to establish the status of indigenous Tswana pigs in the country in terms of their population. The three districts were Kgatleng, Kweneng and South-East. These districts were purposely chosen because they are the ones which have a considerable number of indigenous Tswana pigs. A structured questionnaire was administered to 71 farmers in 2018, 50 farmers in 2019 and 71 farmers in 2020. The population of indigenous Tswana pigs declined over the three years of study. South-East district had the highest number of indigenous pigs and Kweneng district had the least number during the three years of study. Sows and gilts were more than boars. The average herd size ranged from 3.5 to 20 over the three years. According to risk status classification by FAO, the status of indigenous Tswana breed in the southern districts of Botswana is ‘endangered’ and the estimated population growth rate is less than one. There is a strong positive and significant difference between the total number of pigs and the number of female pigs. The regression analysis indicated a positive impact of adult female pig numbers on the total number of Tswana pigs.